Novel Cyanobacterial Diversity Found in Costa Rican Thermal Springs Associated with Rincon de la Vieja and Miravalles Volcanoes: A Polyphasic Approach - Brenes Guillén, Laura Natalia (2020)
Central America is one of the most important biodiversity hot spots in the world, and Costa Rican microbial communities from thermal springs are the best characterized in the isthmus. Miravalles is an inactive quaternary stratovolcano, and the Rincón de la Vieja is a unique active volcano, in whose slopes diverse hydrothermal springs, such as Las Lilas, are located. These springs harbor extensive microbial mats, whose diversity has been studied. Based on their importance as primary producers, in this study we focused on cultured cyanobacterial diversity from two geothermal environments of northern Costa Rica. Several cultural, molecular and taxonomic techniques were employed to maximize the results of a polyphasic approach. Sample collection sites were physicochemically described, and strains were isolated and characterized by light and electron microscopy. Phylogenetic analysis was performed using 16S rRNA gene sequences and amplified ribosomal DNA restriction analysis (ARDRA). Fifty‐six phylotypes were isolated and classified into 21 morphotypes and identified in 14 genera, some of them might be new species within these genera. Furthermore, according to phylogenetic analysis, there are three possible new genera in our collection. Miravalles and Las Lilas thermal springs are reservoirs of novel phylogeographic lineages of phototrophic microorganisms. This study is the first report of strains that belong to the genera Gloeocapsa, Stanieria, Microseira, Klisinema and Oculatella isolated from thermal springs and growing at temperatures above 50°C. We also obtained isolates assigned to Synechococcus, Leptolyngbya spp., and Fischerella, which are considered typical strains in these environments.